Agricultural Development in Asia Potential Use of Nano-Materials and Nano-Technology - Asaduzzaman, Md; Afroz, Mafruha (IntechOpen, 2022)
Agricultural Development in Asia - Potential Use of Nano-Materials and Nano-Technology provides interesting research and information on the use of nanomaterials and nanotechnology for sustainable agriculture in Asia. Chapters discuss the potential use of nanomaterials, nanofertilizers, and nanopesticides for sustainable agricultural development; development of a new generation of nanopesticides for crop protection and plant growth-promoting rhizobacteria; the role of allelopathy for sustainable crop production; and the use of plant materials in livestock farming.